The sensitivity problem of the structure with response functional is the reliability - Pho, Nguyen Van (Vietnam Journal of Mechanics, 1994)
In this paper, the structural design sensitivity analysis is considered, in which the reliability is response functional. The author sets up the problem, proposes some methods for solving and apply the obtained results to a simple example.